Implementation of Topsis Method for Supervisor Selection Decision Making System at District 10 Restaurant And Bar - Emasopangidoan Waruwu Emasopangidoan (Sean Institute, 2021)
Management of Resources Manuasion of a company greatly influences many aspects of determining the success of the company. If the company's performance can be organized, all aspects of the company can run Good. The problem in District 10 Restaurant And Bar in choosing a supervisor is to use measurements based on the aspects and criteria desired and achieved by the company. So that in the process of selecting the pervisor only based on the direct behavior that is considered senior, but there is a fact that it cannot contribute more to the company and there is no specific method used in selecting Supervisors, so that the assessment is not appropriate. To overcome this problem, a computer system is needed that helps the Supervisor by using the Topsis Method TOPSIS (Technique for Others Reference to Ideal Solution). It will rank all alternatives to positive alternative solutions that have been ranked and then used as a reference for decision making, namely decision support system takes the decision to choose the best solution that is desired.